Transformational leadership and the development of professional learning communities in elementary schools - Aziz, Cut Nurhalizah; Rahyasih, Yayah; Abubakar, Abubakar; Nurdin, Nurdin (Journal of Educational Management and Instruction (JEMIN), 2025)
Transformational leadership has become increasingly vital in education for fostering school improvement, innovation, and teacher collaboration. This study aimed to describe how transformational leadership is implemented by elementary school principals and how it contributes to the development of Professional Learning Communities (PLCs). Conducted at SDN 019 Pabaki Bandung, West Java province of Indonesia, this study employed a qualitative case study design. Data were gathered through purposive sampling from three participants: a principal, a vice principal, and a teacher. Methods included interviews, direct observations, and document analysis. Triangulation and inductive analysis were used to ensure data validity and depth. The findings reveal that the principal's transformational leadership significantly improved teacher collaboration, instructional quality, and administrative efficiency. The development of PLCs was evident through continuous, collaborative learning practices supported by the principal's guidance, encouragement of innovation, and cultivation of a supportive school culture. These practices fostered a harmonious and innovative environment conducive to ongoing professional growth. This study underscores the importance of transformational leadership in empowering educators and sustaining PLCs. The findings highlight the role of school leaders in promoting continuous learning and collaboration, ultimately contributing to improved educational quality. The implications suggest that adopting transformational leadership can serve as a catalyst for meaningful school reform and long-term professional development.